Investigation of Thermodynamic Properties in ZnTe, ZnSe, ZnS Crystals using ab initio Calculations - Galushchak, M.O.; Boychuk, V.M.; Nykyruy, L.I.; Parashchuk, T.O. (Physics and Chemistry of Solid State, 2015)
Using cluster models for cubic sphalerite for stoichiometric ZnX, X = S, Se, Te crystal was spent calculation of values of thermodynamic parameters under normal conditions, and was defined the analytical expressions of temperature dependences of energy ΔE and enthalpy ΔH, Gibbs free energy ΔG, entropy ΔS. It was calculated temperature dependences of the Debye temperature ΘD. The correlation beetwen thermodynamic (ΔE, ΔH, ΔG, ΔS), heat (Cv, Cp, ΘD) parameters of ideal crystals ZnTe, ZnSe, ZnS and their main fundamental characteristics (band gap Eg, the contribution of ionization δ, electronegativity ΔX, binding energy D, comprehensive compression module B) have been find.